Evaluation of Properties of Cast Metal Foams with Irregular Inner Structure - I. Kroupová; P. Lichý; L. Ličev; J. Hendrych; K. Souček (Archives of Metallurgy and Materials, 2018)
Internal structure of metal foams is one of the most important factors that determine its mechanical properties. There exists a number of methods for studying the nature of the inner porous structure. Unfortunately most of these processes is destructive and therefore it is not possible to reuse the sample. From this point of view, as a suitable method seems to be the ability of using the so-called X-ray microtomography (also micro-CT). This is a non-destructive methodology used in a number of fields (industry, science, archaeology, medicine) for a description of the material distribution in the space (e.g. pores, fillers, defects, etc.). In principle, this technology works on different absorption of X-ray radiation by materials with changing proton number. The contribution was worked out in collaboration with experts from the Faculty of Electrical Engineering and Computer Science of the VŠB-Technical University of Ostrava and it is focused on the analysis of internal structure of the metal foam casting with irregular arrangement of internal pores by using micro-CT. The obtained data were evaluated in the commercial software VGStudio MAX 2.2 and in the FOTOMNG system. For the evaluation of these data a new specialized module was introduced in this system. Several methods of pre-processing the image was prepared for the measurement. This preliminary processing consists, for example, from a binary image thresholding for better diversity between the internal porosity and the material itself or functions for colour inversion.